Lichens of the genus Cladonia in grassland habitats of Ukraine (CHORNOMORSKI BOTANICAL JOURNAL, 2021)
It has been analyzed the distribution of Cladonia P. Browne in the grassland habitats of Ukraine. A total of 39 lichens were identified in grasslands, of which C. asahinae, С. acuminata, C. decorticata and C. conista were new to Ukraine, C. carneola, С. сervicornis, C. floerkeana, та C. polydactyla, С. portentosa та С. scabriuscula – for Mykolaiv region, C. cervicornis – for Donetsk and Kherson region, C. deformis and C. floerkeana – for Rivne region, C. monomorpha – for Donetsk, Kirovohrad, Mykolaiv, Rivne, Kherson and Chernivtsi regions, C. polycarpoides – for AR Crimea, Dnipropetrovsk, Donetsk and Zaporizhia regions, C. rei – for Vinnytsia and Rivne regions, C. subulata – new species for Volyn regions, C. strepsilis – for Donetsk region, С. peziziformis – for Kherson and Mykolaiv regions, C. carneola – for Kirovohrad region. Certain locations of С. grayi are first time reported for Ukraine from Zakarpattia region. Lichens of the genus Cladonia have been identified in 14 grassland habitats. The largest number (23 species) has been found in cryptogam- and annual-dominated vegetation on siliceous rock outcrops (R12) of the Ukrainian Crystal Shield. Fourteen species have been found in the habitats of inland sanddrift and dune with siliceous grassland (R1Q), which are common in northern Ukraine. Twelve species of the genus have been observed in the sandy grasslands of the Pannonian and Pontic sandy steppes (R11) in southern Ukraine. Ten species of the genus have been found in the habitats of continental dry steppe (R1B). Cladonia mitis has a dominant role in inland sanddrift and dune with siliceous grassland (R1Q), C. foliacea and C. rangiformis in grasslands on siliceous rock outcrops (R12), C. foliacea and C. furcata in the Pannonian and Pontic sandy steppes (R11). For some grassland habitat types Cladonia species have diagnostic value: C. carneola, C. monomorpha, C. polycarpoides, C. strepsilis – for R12, C. cervicornis – for R11, C. rei – for R11 та R12, C. macroceras and C. pleurota – for R41 and R43; C. foliacea, C. furcata, C. rangiformis – for R1B, R11 and R12. A key for identifying 50 species of Cladonia genus has been compiled, which highlights the most characteristic features of species for their identification in the field.
Keywords: expert system EUNIS–ESy, sandy grasslands, rocky grasslands, dry continental steppes, diagnostic species.